Acute Transient Macular Edema after Uneventful Cataract Surgery - J. S. Beisekeeva; A. V. Bezrukov; S. A. Kochergin; A. I. Samoylenko (Oftalʹmologiâ)
Purpose: to present analysis a case reports of 17 patients who had an acute transient macular edema appeared straight after uncomplicated cataract surgery.Patients and Methods. Working with literature and retrospective observational case series reviewing clinical and imaging data from 17 patients (17 eyes) with acute transient macular edema.Results. There are several cases of acute macular hole development after cataract surgery (complicated and uncomplicated). Also there are reports of macular odema development after several weeks after uncomplicated phacoemulsification due to pseudophakic cystoid macular oedema (Irvine-Gass syndrome) or due to vitreomacular traction syndrome. We observed a series of transient macular oedema with 3.8 % incidence occurring on the first days after uncomplicated phacoemulsification with IOL implantation that had no signs of vitreomacular traction or aqute inflammation. Men suffer frequently than women (14:3). Systemic hypertension prevailed among these patients (15 from 17). Optical coherence tomography (OCT) was made in patients complaining on blure vision and who had signs of macular edema by ophthalmoscopy. By OCT high neuroepithelium detachment was observed at the first day after uneventful cataract phacoemulsification with intraocular lens implantation in 17 patients with quiet postoperative condition of the eye. The edema resolved on the 3–6-th day by standard phaco accompanying pharmacological treatment. In most cases posterior vitreous cortex was adjacent to the retina except 3 patients with posterior vitreous detachment (PVD) in macular area. We found a paper by Costen M.T.J. et al. (2007) about the same striking appearance of maculopathy called by authors “A-sign” maculopathy because of A-shaped pattern on OCT images in 3 patients after routine cataract surgery. Yaman A (2008) and Panagiotidis D (2010) also reported same findings after uncomplicated cataract surgery. We compared our findings with 3 papers mentioned above, as well as with typical pseudophakic cystoid macular edema (CME or Irvine-Gass syndrome) and vitreomacular traction syndrome. We also discussed possible ethiopathogenesis of thеse cases in terms of morphology of the macula region.Conclusion. This article could improve our understanding of mechanisms of the interstitial fluid flow in the eye tissues.